Antirreceptor encephalitis after surgical resolution of ovaric teratoma: review of the literature about a case - Quintero Marzola, Iván Darío; De Luque Baute, Ray Vicente; De Jesús Quintana Pájaro, Loraine; Mendoza Sánchez, José Francisco; Ramos Villegas, Yancarlos; Pájaro Puerta, Mónica; Moscote Salazar, Luis Rafael (Revista Argentina de Neurocirugía, 2020)
Introduction: NMDA antireceptor encephalitis is an autoimmune pathology generated by IgG antibodies against a glutamate receptor subunit. It can develop independently or associated with tumors such as ovarian teratoma. In these cases, immunotherapy and tumor resection are pillars for the resolution of the picture. We report the first pediatric case of encephalitis subsequent to removal of ovarian teratoma. Case description: A 13-year-old female with a history of resection of right ovarian teratoma who consults for psychomotor agitation, unmotivated laughter, incoherent ideas, persistent headache and involuntary movements of the left hand. Neuroimaging and infectious paraclinics are performed, all within normal range. He was admitted to the ICU with a ventilatory requirement and refractory seizures. Initially managed with antipsychotics, anticonvulsants, antibiotics, and antivirals. A positive test is received for antibodies to the NMDA receptor in the cerebrospinal fluid. Plasmapheresis and human immunoglobulin are indicated. Discussion: NMDA antireceptor encephalitis can produce a clinical picture similar to psychiatric pathologies such as schizophrenia. In the context of an ovarian teratoma, it has been proposed that tumor apoptosis induces the release of antigens and subsequent generation of antibodies capable of crossing the blood-brain barrier, which may remain quiescent even after resection of the tumor. Conclusions: Our case broadens the questions about the pathophysiology of this disease in the patient with a previous history of ovarian teratoma. It is not clear if it is triggered by antibodies present before resection or its appearance is not related to ovarian teratoma.